2022
DOI: 10.3390/horticulturae8030198
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation of Phenylalanine, Glucosinolate, Benzylisothiocyanate (BITC) and Cyanogenic Glucoside of Papaya Fruits (Carica papaya L. cv. ‘Tainung No. 2’) under Different Development Stages between Seasons and Their Correlation with Bitter Taste

Abstract: Papaya fruit is one of economic crops in Taiwan, mostly eaten as table fruits. In some Asian countries, unripe papaya fruit is eaten as salad and this led to trends in Taiwan as well. However, unripe papaya fruit may taste bitter during cool seasons. Glucosinolate and cyanogenic glucoside are among the substances that cause bitter taste in many plants, which can also be found in papaya. However, there is still no report about the relationship between seasons and bitter taste in papaya fruits. Thus, the purpose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Furthermore, the bitterness intensity in cool-season fruits is more significant than in warmseason fruits. In their study, Jioe et al [9] corroborated the previous findings where phenylalanine served as CG and GSL precursor. Based on their calculated correlation values, they also suggested that GSL was not the only component that generated a bitter taste in immature papaya fruits [9].…”
Section: Gsl Compound Structural Formula Plant Speciessupporting
confidence: 78%
See 1 more Smart Citation
“…Furthermore, the bitterness intensity in cool-season fruits is more significant than in warmseason fruits. In their study, Jioe et al [9] corroborated the previous findings where phenylalanine served as CG and GSL precursor. Based on their calculated correlation values, they also suggested that GSL was not the only component that generated a bitter taste in immature papaya fruits [9].…”
Section: Gsl Compound Structural Formula Plant Speciessupporting
confidence: 78%
“…The co-occurrence of GSL and CG in a single plant species was initially thought to be due to the presence of contaminant extracts, as the secondary metabolites were perceived as mutually exclusive [8]. However, several articles reported the existence of both CG and GSL in Carica papaya [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The bitterness was analyzed at the Department of Horticulture (Postharvest group), National Chung Hsing University. The panelists, bitter taste rate and replicates as described in Jioe et al (2022). Ten panelists (four women and six men, average age 20-25 years) participated in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Papaya tree parts could be a good candidate for the phytofabrication of AgNPs given their phytochemicals [30]. Indeed, papaya reportedly contains alkaloids, such as carpain and pseudocarpain; enzymes, such as papain and chymopapain; and other compounds, such as benzyl isothiocyanate or benzyl glucosinolate [33,34]. All of these compounds can have significant roles not only in reducing silver ions (Ag+) to form Ag, but above all as capping and stabilizing element for AgNPs.…”
Section: Introductionmentioning
confidence: 99%